2017
DOI: 10.1093/intqhc/mzx088
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing and assessing improvement capability: a review

Abstract: PurposeThe literature is reviewed to examine how ‘improvement capability’ is conceptualized and assessed and to identify future areas for research.Data sourcesAn iterative and systematic search of the literature was carried out across all sectors including healthcare. The search was limited to literature written in English.Data extractionThe study identifies and analyses 70 instruments and frameworks for assessing or measuring improvement capability. Information about the source of the instruments, the sectors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…The reported outcomes on the organisations are interesting since healthcare improvement capability is an area of much current discussion—it is questioned whether it is possible to increase organisational improvement capability through courses in QI; see for example refs 7 35 36. In a paper by Babich et al 8 it is concluded that hospitals focusing on either projects or staff training had limited value compared with organisations strengthening their organisational systems, structures or processes aimed at improvement efforts.…”
Section: Discussionmentioning
confidence: 99%
“…The reported outcomes on the organisations are interesting since healthcare improvement capability is an area of much current discussion—it is questioned whether it is possible to increase organisational improvement capability through courses in QI; see for example refs 7 35 36. In a paper by Babich et al 8 it is concluded that hospitals focusing on either projects or staff training had limited value compared with organisations strengthening their organisational systems, structures or processes aimed at improvement efforts.…”
Section: Discussionmentioning
confidence: 99%
“…For example—the Health Foundation’s QI evidence scan,48 and Walshe20 both review improvement methodologies using a variety of different terms. We both used a variety of different terms for ‘QI’ within searches to capture QI literature 21 29. We used free-text key words to account for the problem that phrases such as ‘quality improvement’ and ‘continuous improvement’ are sometimes used synonymously.…”
Section: Challenges Of Conducting a Literature Review Systematically mentioning
confidence: 99%
“…Similarly, literature review revealed no accepted definition. Therefore, Furnival et al (2017)29 used Whittemore and Knafl’s integrative review method50 which allows for several perspectives of a topic to be used. Improvement capability was defined as: ‘the organisational ability to intentionally and systematically use improvement approaches, methods and practices, to change processes and products/services to generate improved performance.’29…”
Section: Challenges Of Conducting a Literature Review Systematically mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a substantial relevant literature, in healthcare and other sectors, on what has been termed improvement capability, defined for the purposes of this paper as ‘the organisational ability to intentionally and systematically use improvement approaches, methods and practices, to change processes and products/services to generate improved performance’ [10] (p. 5). This definition comes from a recent integrative review of improvement capability by Furnival et al which highlighted the absence of empirically tested and validated frameworks for assessing improvement capability and identified a number of competing definitions and 70 different assessment tools or frameworks with somewhat divergent underlying theoretical models, constructs and measurement items.…”
Section: Introductionmentioning
confidence: 99%